United Republic of Tanzania : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper ;, 2005)
Tanzania reached the completion point under the enhanced HIPC Initiative on November 21, 2001. Staff is of the view that all criteria have been met, and recommends that the Board determine that Tanzania qualifies for immediate debt relief under the MDRI.